Key Success Factors of Digital Transformation - Krhač Andrašec, Eva; Urh, Benjamin (Vloga naprednih tehnologij v inženiringu poslovnih sistemov, 2025)
The chapter examines the multidimensional digital transformation process in various sectors, from artificial intelligence to digital twins and the transition to smart factories. Digital transformation is a change or shift in operational and strategic frameworks needed by the rapid advancement in digital technology. The term stands for a holistic approach in which digital technology is fully integrated into all business areas by radically adapting organizational activities and providing added value to customers. We have found that digital transformation is more than just implementing technology. It requires a cultural shift towards constant experimentation and openness to failure. Such changes make the organization agile, efficient, and customer-centric, with the ability to quickly integrate new data-driven insights into the overall decision-making and innovation process. The chapter describes the challenges and critical factors companies face in digital transformation based on a detailed literature review and case studies.